Masculinities and the law : a multidimensional approach - Cooper, Frank Rudy; McGinley, Ann C.; Kimmel, Michael S. (New York : New York University, 2016)
According to masculinities theory, masculinity is not a biological imperative but a social construction. Men engage in a constant struggle with other men to prove their masculinity. This title develops a multidimensional approach. The book argues that multidimensional masculinities theory can change how law is applied.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Masculinity; Feminist theory; Race; Men -- Legal status, laws, etc; Society; Society & culture: general; Feminism & feminist theory; Gender studies: men & boys; Jurisprudence & general issues; Legal skills & practice